Right to water in peasant and indigenous communities: Ecuador case - Isch, Edgar (2023)
Water management in Ecuador has significant experience from prehistoric times to the present, where scenarios such as the recognition of ancestral conservation strategies, struggles for access and control from sectors of power, legal approaches that in the new Constitution confer the right and order of priority to water, and others. It is necessary to review compliance with the right to water in peasant and indigenous communities, which has historically been restricted, causing situations of water injustice in the communities that live in the territories where the water is born. Ecuador's legal system grants rights to nature and water, but it must also ensure the right of the population to enjoy water as a fundamental right, in a context of respect and appreciation of worldviews for their care. This article begins with a historical perspective in which changes and loss of rights are observed in the neoliberal phase, to give way to the formal recovery of those rights linked with a legal pluralism, which today leaves new challenges for the whole social and nationalities and indigenous peoples in particular.